The relationship between task factors and occupational safety and health (OSH) performance in the printing industry - Mohd Nasir Selamat,; Mukhiffun Mukapit, (Penerbit Universiti Kebangsaan Malaysia, 2018)
In Malaysia, studies had shown that the low workers performance occurreddue to Occupational Safety and Health (OSH) related aspects such as occurrences accidents, absenteeism, higher level of sickness and stress at work.The long run of this situation will effect organization performance and reduce the quality of work, increase the cost of worker’s compensation and eventually troubling the development of organization. This study examines the task factors related to work demand in enhancing OSH performance, measured in term of occupational accident, occupational stress, sickness of workers and absenteeism focused in the Malaysian Printing Industry.Two hundred and ninety-five respondents from several printing companies in Malaysia were analyzed through distributed questionnaires. Three dimensions involved as independent variables to measure task factors referred to quantitative demand, emotional demand and sensorial demand, while OSH performance as dependent variables measured by occupational stress, occupational accident, absenteeism and sickness.Higher work demand contributes to worker’s stress and accidents that leads to absenteeism problem. Sickness problem confirmed result in influencing absent issues. Moreover, result concern related behavioural aspect which attention should be given on the developing behavioural intervention in order to enhance worker’s knowledge, attitude, and skill while performing their work.Changes related in practicing Human Resource Management (HRM) aspect especially on OSH factors at work such as balancing working hours, altering work condition and environment, enforcing ergonomic aspects, implementing OSH training and safety culture, will help to ensure employees’ safety and health performance. Future research and limitations of the study is discussed.